Influences of feedstock and plasma spraying parameters on the fabrication of tubular solid oxide fuel cell anodes - Yang, Yung Chin; Wang, Po Hao; Tsai, Yu Ting; Ong, Hwai Chyuan (Elsevier, 2018)
This study developed a tubular solid oxide fuel cell (SOFC) anode support layer via atmospheric plasma spraying, which is considered one of the most promising methods for producing SOFCs because of its faster deposition rate and lower cost compared with other film formation processes. Plasma spraying can replace the traditional use of extrusion technology to manufacture the anode base tube, eliminating the need for high-temperature sintering steps. In this study, commercially available powders were used to make the anode of a tubular SOFC from NiO/yttria-stabilized zirconia (YSZ) powder, and Na2CO3 and polymethyl methacrylate were tested as pore-forming agents. The anode composite powder was sprayed on the graphite base pipe, and the final product was changed by altering the spraying parameters and anode powder ratio. The direct current (DC) resistance measurements showed that the conductivity of the Ni/YSZ tubular anode formed with higher power plasma spraying could reach 428.55 S/cm at 800 °C. The experimental results showed that the power and parameters of atmospheric plasma spraying could affect the porosity and electron conductivity of tubular SOFC anodes.